Stochastic Frontier Production Function an Application of the Coconut Farms in Coimbatore District - Selvam, G; Mathevan Pillai, K; K.Abirami, S (International Journal of Engineering and Technology, 2018)
In most of the developing countries agriculture is a source of livelihood and sustenance for majority of the people and its growth provides the greatest hope for improving the living standards of the people.Â It provides food for the population and raw materials capital and labour to other sectors of the economy.Â Thus the development of agriculture plays a major role in total economic development of a country.Â Hence formulation of agricultural development strategies needs much care and attention.